EVALUATION OF THE ANTI-INFLAMMATORY ACTIVITY OF COMBINATION OF ETHANOL EXTRACTS OF AZADIRACHTA INDICA (NEEM) AND LAWSONIA INERMIS (HENNA) - Rao ANNAVARAPU, Tirupathi; P, Renuka; P, Akhil; P, Divya; Priyanka P, Devi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The aim of the present study was to investigate the in vitro anti-inflammatory activity of Azadirachta indica (neem) and Lawsonia inermis (henna) individual extract and in combination using the same solvent. Methods: The leaf material of A. indica and L. inermis was collected from surroundings of Aditya College of Pharmacy, Kakinada, East Godavari. Powdered material was subjected to successive solvent extraction process. The yield was collected and prepared different concentrations (50, 100, and 200 Î¼g/ml) of plant extracts. Diclofenac sodium was used as standard drug. The anti-inflammatory activity was performed by in vitro methods such as albumin denaturation method and human red blood cells membrane lysis method. Results: Denaturation of proteins is a well-documented cause of inflammation. Neem showed a significant membrane stabilizing activity of 46.62% and protein denaturation inhibition activity of 57.32% at concentration of 200 Î¼g/ml. Henna showed a significant membrane stabilizing activity of 39.89% and protein denaturation inhibition activity of 53.75% at 200 Î¼g/ml. In combination, both the extracts showed a significant membrane stabilizing activity of 56.63% and protein denaturation inhibition activity of 67.69% at concentration of 200 Î¼g/ml. Conclusion: The present study concluded that combination of A. indica and L. inermis possesses significant anti-inflammatory activity when compared with individual extract. Keywords: Anti-inflammatory, Human red blood cell, Protein denaturation, Lawsonia inermis, Azadiracta indica.